Techniques of financial analysis : - Helfert, Erich A . (Richard D. Irwin, 1997)
The book presents the fginancial concepts and tools that are essential in making fundamental business decisions. It shows how to understand the business system; management operating funds; analyze and project financial performance; model financial dynamics; choose financing alternatives; evaluate business investment; place investments in strategic perspective; understand the cost of capital; value a business and its parts; manage for shareholder value. Also the book has been updated to include more emphasis on the following modern topics: shareholder value creation, importance of economic thinking, cash flow analysis, and risk analysis and management